Rhizobium strains competitiveness on bean nodulation in Cerrado soils - Raposeiras, Ruy; Marriel, Ivanildo Evódio; Muzzi, Maria Rita Scotti; Paiva, Edilson; Filho, Israel Alexandre Pereira; Carvalhais, Lilia Costa; Passos, Raul Vinícius Magalhães; Pinto, Patrícia Pereira; Sá, Nadja Maria Horta de (Pesquisa Agropecuaria Brasileira, 2006)
The objective of this work was to identify the most competitive and effective Rhizobium strains in order to increase common bean yield by nitrogen fixation as alternative or complementation to the nitrogen fertilization. Competitiveness tests were lead in axenic conditions, in Cerrado soil pots and in three field experiments, with native Rhizobium strains that were previously identified, according to their effectiveness and genetic variability. The identification of strains in nodules was performed using serological tests (axenic conditions) – agglutination and enzyme linked immunosorbent (Elisa) assays – and random amplified polymorfic DNA (RAPD) (Cerrado soil). Plant yield was determined using the dry weight (greenhouse conditions), total N and grain yield (field experiments). Among the analyzed Rhizobium strains, native strain SLA 2.2 and commercial strain CIAT 899 were the dominant nodules in plants of the most productive plots, presenting yield productivity similar or higher to those obtained in treatments where 20 kg ha-1 of N were applied.